Short-wall paste continuous mining and continuous backfilling for controlling industrial square surface subsidence - Meng, Zixuan; Dong, Yue; Zhang, Xinguo; Jiao, Fangshu; Fan, Yaqi; Thammavongsa, Champa (Frontiers in Earth Science, 2023)
To facilitate coal mining under the industrial square in Western China, short-wall paste continuous mining and continuous backfilling (PCMCB) is proposed to release the overlaid resources and handle coal gangue. First, the concept of short-wall PCMCB is presented, and the principle of surface subsidence is analyzed. Second, the mechanical model of the branch roadway and strength of the backfill body are established via mechanical derivations. Third, the proportion of backfill materials is calculated. Finally, field applications are carried out in the Dingjiaqu coal mine. The results show the following: 1) Based on the simply supported beam model of the roof and strength design model of the backfill body, the reasonable width of the branch roadway was determined as 5 m and late strength of the backfill body should exceed 2.62 MPa in the Dingjiaqu coal mine. 2) According to the design strength of the backfill body and backfill material proportion, the reasonable ratio of cement: fly ash: gangue: water was determined as 1:1.82:4.17:1.78. 3) In accordance with the equivalent mining height theory, the critical filling rate of the goaf should be more than 90% to ensure that the deformation is within the first level of building damage. 4) The field application shows that subsidence could be effectively controlled by backfilling, the overall surface subsidence was very small, and the maximum subsidence value (77 mm) was far lower than the deformation extremes of the building protection requirements. This study provides practical guidance for the exploitation of overlaid resources under similar shallow burial conditions, which can help in the disposal of coal gangue with considerable social and economic benefits with popularization and application.